Southern westerlies in LGM and future (RCP4.5) climates - Chavaillaz, Y.; Codron, F.; Kageyama, M. (Climate of the Past, 2013)
International audience Mid-latitude westerlies are a major component of the atmospheric circulation and understanding their behaviour under climate change is important for understanding changes in precipitation, storms and atmosphere-ocean momentum, heat and CO2 exchanges. The Southern Hemisphere westerlies have been particularly studied in terms of the latter aspects, since the Southern Ocean is a key region for the global oceanic circulation as well as for CO2 uptake. In this study, we analyse, mainly in terms of jet stream position, the behaviour of the southern westerlies for the Last Glacial Maximum (LGM, 21 000 yr ago, which is the last past cold extreme) and for a future climate, obtained after stabilisation of the RCP4.5 scenario. The a priori guess would be that the behaviour of the westerly jet stream would be similar when examining its changes from LGM to pre-industrial (PI) conditions and from PI to RCP4.5, i.e. in both cases a poleward shift in response to global warming. We show that this is in fact not the case, due to the impact of altitude changes of the Antarctic ice sheet and/or to sea ice cover changes. © Author(s) 2013.